Capital flows and economic growth revisited: evidence from five Sub-Saharan African countries. Issue 5 (3rd September 2018) - Adams, Samuel; Klobodu, Edem Kwame Mensah
ABSTRACT: The study examines the differential effects of capital flows on economic growth in five Sub-Saharan African (SSA) countries over the period 1970–2014. Using the autoregressive distributed lag methodology, the findings show that in the long-run capital flows (i.e. foreign direct investment (FDI), aid, external debt, and remittances) have different effects on economic growth. FDI has a significant positive effect in Burkina Faso and negative effects in Gabon and Niger whereas the impact of debt is negative in all countries. Aid, however, promotes growth in Niger and Gabon whiles it deters growth in Ghana. Remittances, on the other hand, have a significant positive effect in Senegal. Finally, gross capital formation is significant in most of the countries and the impact of trade is mixed. These results suggest that the benefits of capital flows in SSA have been overemphasized.